Performance of the time‐resolved ultra‐small‐angle X‐ray scattering beamline with the Extremely Brilliant Source. Issue 1 (19th January 2022) - Narayanan, Theyencheri; Sztucki, Michael; Zinn, Thomas; Kieffer, Jérôme; Homs-Puron, Alejandro; Gorini, Jacques; Van Vaerenbergh, Pierre; Boesecke, Peter
Abstract : The new technical features and improved performance of the time‐resolved ultra‐small‐angle X‐ray scattering beamline at the ESRF are presented. The beamline enables static and time‐resolved investigations from ångström to micrometre size scales down to the sub‐millisecond time range and coherent scattering studies in the ultra‐small‐angle region. Among the main applications are the elucidation of static and transient hierarchical structures in soft matter and biophysical systems, and the dynamics of out‐of‐equilibrium complex fluids. Abstract : The new technical features and enhanced performance of the ID02 beamline with the Extremely Brilliant Source (EBS) at the ESRF are described. The beamline enables static and kinetic investigations of a broad range of systems from ångström to micrometre size scales and down to the sub‐millisecond time range by combining different small‐angle X‐ray scattering techniques in a single instrument. In addition, a nearly coherent beam obtained in the high‐resolution mode allows multispeckle X‐ray photon correlation spectroscopy measurements down to the microsecond range over the ultra‐small‐ and small‐angle regions. While the scattering vector (of magnitude q ) range covered is the same as before, 0.001 ≤ q ≤ 50 nm −1 for an X‐ray wavelength of 1 Å, the EBS permits relaxation of the collimation conditions, thereby obtaining a higher flux throughput and lower background. In particular, a coherent photon flux in excess of 10 12 photons s −1 can be routinely obtained, allowing dynamic studies of relatively dilute samples. The enhanced beam properties are complemented by advanced pixel‐array detectors and high‐throughput data reduction pipelines. All these developments together open new opportunities for structural, dynamic and kinetic investigations of out‐of‐equilibrium soft matter and biophysical systems.